Microbial Kinetics and Enzymatic Activities in Hybrid Moving‐Bed Biofilm Reactor‐Membrane Bioreactor Systems. Issue 6 (23rd March 2016) - Leyva‐Díaz, Juan Carlos; González‐Martínez, Alejandro; Calderón, Kadiya; González‐López, Jesús; Muñío, María del Mar; Poyatos, José Manuel
Abstract: A membrane bioreactor (MBR), a hybrid moving‐bed biofilm reactor‐membrane bioreactor (hybrid MBBR‐MBRa ) containing carriers in the anoxic and aerobic compartments, and a hybrid MBBR‐MBRb containing carriers only in the aerobic zone were used in parallel and compared for treating municipal wastewater. The microbial kinetics and the evolution of the enzymatic activities of α ‐glucosidase and acid and alkaline phosphatase as well as the bacterial diversity and bacterial community structure were studied to explain the removal of organic matter and nutrients. The MBR and the hybrid MBBR‐MBRb showed the highest reduction percentages of chemical oxygen demand. Moreover, the hybrid MBBR‐MBRb exhibited the highest removal performance of total nitrogen. Abstract : The kinetic parameters regarding heterotrophic and autotrophic biomasses in a membrane bioreactor and two hybrid moving‐bed biofilm reactor‐membrane bioreactors were evaluated and related to organic matter and nutrient removals. Evolutions of enzymatic activities in the suspended and attached biomasses were analyzed to determine the effect of the biofilm in the hybrid system.